Rising Expectations: Access to Biomedical Information - Lindberg, D. A. B.; Humphreys, B. L. (Yearbook of Medical Informatics, 2008)
Objective To provide an overview of the expansion in public access to electronic biomedical information over the past two decades, with an emphasis on developments to which the U.S. National Library of Medicine contributed.Methods Review of the increasingly broad spectrum of webaccessible genomic data, biomedical literature, consumer health information, clinical trials data, and images.Results The amount of publicly available electronic biomedical information has increased dramatically over the past twenty years. Rising expectations regarding access to biomedical information were stimulated by the spread of the Internet, the World Wide Web, advanced searching and linking techniques. These informatics advances simplified and improved access to electronic information and reduced costs, which enabled inter-organizational collaborations to build and maintain large international information resources and also aided outreach and education efforts The demonstrated benefits of free access to electronic biomedical information encouraged the development of public policies that further increase the amount of information available.Conclusions Continuing rapid growth of publicly accessible electronic biomedical information presents tremendous opportunities and challenges, including the need to ensure uninterrupted access during disasters or emergencies and to manage digital resources so they remain available for future generations.
Keywords: Access to information; genetic databases; digital libraries; consumer health information; clinical trials